Implementing a Tivoli solution for central management of large distributed environments - Moeller, Morten (IBM redbooks., 2005)
Deploying and managing distributed systems in hundreds or thousands of branch banks and retail stores, called outlets, requires careful planning of the automation to cope with the sheer numbers of systems involved. This IBM Redbooks publication demonstrates how to architect, establish, and configure a Tivoli systems management environment that supports the central management of thousands of outlet systems based on the open United Linux platform. The main focus of this book is to provide step-by-step instructions, sample scripts, and code to install and deploy the core Tivoli products that enable the organization to: - Deploy and maintain distributed application solutions - Monitor availability and performance of remote systems, middleware components and applications - Perform diagnostics and troubleshooting of remote system and application components to resolve availability or performance issues - Gather metrics to document performance levels This book is intended for IT professionals with a basic understanding of the core Tivoli product set and who are responsible for deploying a Tivoli management infrastructure. Please note that the additional material referenced in the text is not available from IBM.